Robot-assisted laparoscopic treatment of appendicovesical fistula in a child: a case report and literature review - Fang, Zheng; Sun, Yi; Wang, Zhongxu; Yan, Xiangming; Zhang, Ting; Cao, Xu; Wang, Tianyi; Wang, Hongchao; Liu, Jun; Feng, Ting; Dai, Shu (Frontiers in Pediatrics, 2025)
Appendicovesical fistula (AVF) is a rare condition that occurs in children characterized by an abnormal communication between the appendix and the bladder, caused by diseases such as inflammation or malignancy. Due to the lack of specific clinical symptoms and the difficulty in confirming the diagnosis with traditional imaging examinations such as ultrasound and CT, the disease often has a protracted course. This paper reports a case of a pediatric case of AVF presenting with dysuria, urinary frequency, and diarrhea. The diagnosis was confirmed by contrast-enhanced ultrasound (CEUS), and the patient successfully underwent robot-assisted laparoscopic partial cystectomy and appendectomy without postoperative complications. This case demonstrates an innovative application of CEUS combined with robot-assisted laparoscopic surgery for the diagnosis and treatment of a pediatric case of AVF. In addition, we conducted a literature review on AVF in children.